The Regulation of Disorgement in the Indonesia Capital Market: Remaining Concerns and Lessons from US (Journal of Indonesian Legal Studies, 2022)
This study aimed to analyse the authority that recently empowered the Indonesia Financial Services Authority (OJK) based on OJK Regulation Number 65/POJK.04/2020 in conjunction with OJK Circular 17/SEOJK.04/2021. OJK was empowered to pursue disgorgement in the Indonesian capital market as a new tool for protecting investors by analyzing changes in disgorgement enforcement practices in the US. This study used a doctrinal legal method with a comparative approach. The comparative approach was used to examine the possibility of strengthening disgorgement enforcement applicable to current Indonesian law on such practices in the US. Disgorgement in Indonesia is similar to the previous one in the US. The disgorgement authority in the Capital Market Act was not explicit because OJK still interpreted “written orders” such as “grant relief ancillary to an injunction” when disgorgement was first introduced by the SEC. This poses challenges in calculating the number of disgorgements that may be limited or canceled due to a lack of strong legal remedies when the violator does not pay the disgorgement. Considering practical experience in the US from Texas Gulfur Sulfur to Kokesh and Liu, disgorgement in Indonesia needs strengthening to maintain enforcement sustainability and avoid setbacks. Therefore, the strengthening should involve placing the disgorgement authority in the Capital Market Act, providing Standard Guidelines for the Calculation of Disgorgement Amounts and and establishing regulations on Procedures for Civil Lawsuits by OJK. The results are expected to be a reference for regulators and legislators to improve enforcement of the disgorgement regime in Indonesia.